Electrophoretic Deposition of Single Wall Carbon Nanotube Films and Characterization. Issue 1752 (2014) - Lim, Junyoung; Jalali, Maryam; Campbell, Stephen A.
ABSTRACT: Electrophoretic deposition enables the rapid deposition of single wall carbon nanotube films at room temperature. An accurate, reproducible film thickness can be obtained by controlling electric field strength, suspension concentration, and time. To investigate the electrical and mechanical properties of such films, we recorded electric resistance and Young's modulus using I-V characterization and a nanoindenter, respectively. The measured resistivity of the films varied from 2.14 × 10 -3 to 7.66 × 10 -3 Ω·cm, and the Young's modulus was 4.72 to 5.67 GPa, independent of film thickness from 77 to 134 nm. These results indicated that the mechanical and electrical properties of film are comparable with previously reported methods such as layer by layer deposition even though we achieved much higher deposition rates. We also measured the film mass density which is usually unrecorded even though it is an important parameter for MEMS/NEMS device actuation. The film density was found with conventional thickness measurement and Rutherford backscattering spectrometry. It varied from 0.12 to 0.54 g/cm 3 as the film thickness increased. This method could be extended to applications of CNT films for flexible electronics or high frequency RF MEMS devices.